Thermal properties of poly(methyl methacrylate-co-butyl acrylate-co-acrylic acid) modified with divinyl benzene and vinyltrimethoxysilane. Issue 2 (1st February 2016) - Chee, Swee Yong; Lee, Meng Keong; Lee, Chee Leong
ABSTRACT: The effect of butyl acrylate (BA), divinyl benzene (DVB) and vinyltrimethoxysilane (TMVS) on the thermal properties of poly(methyl methacrylate- co -butyl acrylate- co -acrylic acid) was investigated. Glass transition temperature ( Tg ), melting temperature ( Tm ) and specific heat capacity of the copolymers were investigated using Differential Scanning Calorimetry. Thermal stability of the copolymers which is associated with the degradation temperature ( Td ) was studied by Thermogravimetric Analysis. Polyacrylates with Tg ranges between -19°Cand 19°C were obtained. With the incorporation of >7 wt% of DVB, the Tg of the copolymer increases from about −17°C to −10°C even though they have not undergone UV irradiation. Gel content results prove that crosslinking has occurred in the copolymers. With increasing amount of TMVS from 0 wt% to 7 wt%, the Tm of the copolymers prepared at acidic pH is about 40-60°C higher than that at the alkaline pH. However, the addition of TMVS gives no significant effect to the Tg and Td of the copolymer films. The thermal stability of the copolymer has improved with increasing amount of BA and DVB, with DVB being more effective. The highest Td of 425°C with 8% of DVB has been obtained. Consequently, a polyacrylate copolymer with a Tg of about −13°C, a Tm of 170 °C and a Td of about 424°C has been successfully synthesized. Hence, the soft polyacrylate with its relatively high Tm and Td could serve as a superb material especially to be applied in the areas that require high melting temperature and good thermal stability.